Analisis Sistematis Corak-corak Tafsir Periode Pertengahan antara Masa Klasik dan Modern-Kontemporer - Nana Najatul Huda (UIN Sunan Gunung Djati Bandung, 2022)
As the treasures of the science of interpretation developed among classical and medieval scholars, many commentators interpreted the Qur'an according to their background or scientific expertise. Therefore, it is important to examine the methods, sources, characteristics and styles of interpretation, especially on the interpretation style which is the subject of this research, in order to facilitate or assist contemporary scholars to find appropriate references or sources on one main topic or problem. The purpose of this study is to discuss the pattern of interpretation in the study of the science of interpretation. This research method is qualitative. The results and discussion of this study indicate that there are several forms of intellectual expression of commentators in expressing the intentions contained in the Qur'an according to the knowledge abilities possessed by the commentators, such as linguistic styles, fiqh, philosophy, tasawuf, i'tiqadi and 'ilmi. So that several exegetes have been born with various knowledge in them, including al-Zamakhsyari, al-Qurtubi and so on. This study concludes that the style of interpretation that was present in the Middle Ages was an achievement between the classical and modern-contemporary periods.